PENGARUH PENGGUNAAN MODEL PROBLEM BASED LEARNING (PBL) TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PESERTA DIDIK KELAS IV SD NEGERI 013 PETAI BARU KABUPATEN KUANTAN SINGINGI - Erza Mulia Agustin; Alexander Alim, Jesi; Hainul Putra, Zetra (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The mathematical problem solving ability (KPMM) of students in elementary schools still tends to be not optimal. The purpose of this research is to find out how learning with the PBL model affects students' KPMM. Pre-experiment research with the type of one group pre-test and post-test design was used to obtain data through quantitative methods. The research subjects were 23 fourth grade students of SD Negeri 013 Petai Baru. Data collection techniques include test questions before and after application (pretest-posttest). The Paired Sample T-Test test with the help of IBM SPSS 25 was used to evaluate how well the Problem Based Learning (PBL) model affects students' KPMM. The results of the analysis using the Paired Sample T-Test test showed a significant positive effect after the application of the Problem Based Learning (PBL) model to fourth grade students of SD Negeri 013 Petai Baru, the Sig value. (2-tailed) of 0.000 shows a smaller number than 0.05 so that the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted.’